Amyloid β peptide promotes bone formation by regulating Wnt/β‐catenin signaling and the OPG/RANKL/RANK system. Issue 3 (16th January 2020) - Yang, Bu; Li, Shangfu; Chen, Zheng; Feng, Feng; He, Lei; Liu, Bin; He, Tianwei; Wang, Xuan; Chen, Ruiqiang; Chen, Zihao; Xie, Peigen; Rong, Limin
Abstract: Background: Amyloid β peptide (Aβ) is involved in osteoporosis, but the effects of Aβ on osteoblast and bone formation remain unclear. In this study, we investigated the effect of Aβ on bone formation. Methods: An animal model of osteoporosis was established by ovariectomy in C57BL/6 mice. The mice received intraperitoneal injection of Aβ. The effect of Aβ on the osteogenic differentiation of human bone marrow stromal stem cells (hBMSCs) and differentiation of both pre‐osteoblasts and pre‐osteoclasts in a co‐culture system were investigated. Results: In the animal study, intraperitoneal injection of Aβ for 8 weeks promoted early and late osteogenic differentiation of hBMSCs. Aβ treatment significantly elevated osterix + (osteoblastic) cells but decreased TRAP + cells (osteoclasts) in the distal femur bone. In vitro study showed that Aβ treatment significantly enhanced matrix mineralization and osteogenic markers (Runx2 and osteocalcin). Aβ treatment activated Wnt/β‐catenin signaling in hBMSCs. The effect of Aβ was blocked by DKK1 (a Wnt/β‐catenin inhibitor) treatment. In the co‐culture system, Aβ treatment significantly increased the ALP activities of MC3T3‐E1 cells (pre‐osteoblasts) but reduced the TRAP + RAW264.7 cells (pre‐osteoclasts). Aβ treatment upregulated TCF1 and OPG proteins in MC3T3‐E1 cells. Aβ treatment upregulated IκB‐α but downregulated NFATc1protein in RAW264.7 cells. These effects were blocked by XAV‐939 (a Wnt signaling antagonist), and then rescued by additional Wnt3a (a Wnt agonist). Conclusion: Aβ treatment simultaneously promoted osteogenic differentiation via Wnt/β‐catenin signaling, and inhibited osteoclasts differentiation via the OPG/RANKL/RANK system, suggesting Aβ is a positive regulator of osteoblast differentiation and bone formation.